ADAPTATION OF TRADITIONAL MINAHASA ARCHITECTURE IN MALANG CITY - Moses Rondonuwu, Yesaya; Wahjutami, Erlina Laksmiani (Border: Jurnal Arsitektur, 2024)
Geographically and climatically, Minahasa and Malang are similar, being in the highlands and having a two-season climate, but Minahasa is more likely to experience seismicity than Malang. Culturally, the Minahasa tribe upholds mapalus to strengthen kinship. From these conditions, there is an adaptation that adjusts to the new environment which aims for comfort in occupying. This research aims to determine the results of geographical, climatic, and cultural adaptation of traditional Minahasa architecture in Malang City. The research method is descriptive qualitative and interviews by analyzing data in the form of comparing aspects of venustas, firmity, and utility. The findings of this research are that the meaning of the three vertical and horisontal spaces has changed slightly, such as the use of the lower space and placement of stairways into the pores. The knockdown system applied can be identified in the connection between the column and the beams, as well as the concrete column that adapts to the environmental conditions. Some have changed in terms of space, structure, and facade as a result of adaptation to the new environment. However, it does not change the main characteristics of Minahasa architecture so that traditional Minahasa architecture can be accepted in Malang.